Pathways to motivation and learning in English language education: a case of two youths engaging in multiliteracies - Colak, Miranda Karjagdi (Emerald Group Publishing Ltd, 2024)
Purpose - This study investigates the effect of digital multimodal composing (DMC) on student motivation and literacy in English as a Foreign Language (EFL) contexts. It explores how students engaged in creating digital animations to respond to literary texts and the implications for integrating DMC into traditional literacy practices. Grounded in social semiotic theory and Self-Determination Theory, this study aims to understand how digital composing influences student engagement, motivation and literacy development. Design/methodology/approach - Qualitative data were gathered over a six-month period using a combination of student surveys, semi-structured interviews, reflection logs and student-produced scripts/ animations. This study focused on two university students who engaged in multimodal projects as part of their extracurricular EFL activities, examining their processes and reflections. Findings - Students demonstrated strong intrinsic motivation during DMC processes, largely due to the social affordances provided by digital multimodal composing. By combining traditional literacy skills with digital practices, students experienced enhanced creative expression, enhanced meaning-making and a deeper understanding of literary texts through the production and sharing of animated videos. This process promoted both emotional and cognitive engagement, emphasizing the importance of teacher guidance and digital tools in creating a more dynamic and supportive learning environment. Practical implications - This study outlines a practical approach to DMC through a structured process: selecting and reading a book, proposing a change as if requesting it from the author, creating and sharing a video on YouTube to explain the change and reflecting on the experience. This approach can guide educators in designing activities that deepen student engagement, enhance critical thinking and integrate digital tools with traditional learning methods. Originality/value - This study contributes to the understanding of how digital technologies can transform traditional literacy practices, offering insights into the benefits of multimodal composition for language learning and motivation in EFL contexts. It provides practical examples of how students and teachers can leverage digital tools to enhance literacy education and prepare students for 21st-century challenges.
Keywords: Multiliteracies; Language learning; Multimodal composing tasks; Situational motivation; Creating animated videos